2015
DOI: 10.1007/s11250-015-0884-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of bovine immunodeficiency virus in water buffaloes (Bubalus bubalis) from the Amazon region, Brazil

Abstract: Bovine immunodeficiency is a chronic progressive disease caused by a lentivirus that affects cattle and buffaloes. Although the infection has been described in cattle in some countries, including in Brazil, there are only two reports of infection in buffaloes: one in Pakistan and one in Cambodia. The aim of the present study was to survey the occurrence of bovine immunodeficiency virus (BIV) in water buffaloes from the Amazon region, Pará state, Brazil. BIV proviral DNA was surveyed in 607 whole blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 12 publications
2
16
0
4
Order By: Relevance
“…These results, when compared to other studies done in the country, showed that the regions tested in the state of Minas Gerais presented a very similar occurrence of BIV infections found by serology and molecular methods in studies carried out in the states of Mato Grosso do Sul and Rio Grande of the South (Meas et al, 2002) and higher than the average found in buffalo in the state of Pará (4.4%) (Albernaz et al, 2015). This percentage was also higher than the values observed by direct detection through PCR in India (8.8%) and moderately similar to the serology studies conducted in Japan (11.7%) (Meas et al, 1998;Patil et al, 2003).…”
supporting
confidence: 79%
See 3 more Smart Citations
“…These results, when compared to other studies done in the country, showed that the regions tested in the state of Minas Gerais presented a very similar occurrence of BIV infections found by serology and molecular methods in studies carried out in the states of Mato Grosso do Sul and Rio Grande of the South (Meas et al, 2002) and higher than the average found in buffalo in the state of Pará (4.4%) (Albernaz et al, 2015). This percentage was also higher than the values observed by direct detection through PCR in India (8.8%) and moderately similar to the serology studies conducted in Japan (11.7%) (Meas et al, 1998;Patil et al, 2003).…”
supporting
confidence: 79%
“…In Brazil, BIV has been detected in cattle from the states of Mato Grosso do Sul and Rio Grande do Sul using PCR and through the detection of antibodies to the capsid p26 protein by Western Blot (Meas et al, 2002). BIV was also detected using semi-nested PCR in peripheral blood leukocytes of buffaloes from the Amazon region (Albernaz et al, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The BIV genome, similar to human immunodeficiency virus (HIV) and other lentiviruses, contains the structural genes gag, pol, env and several accessory genes tat, rev, vif, vpw, vpy, and tmx. However, although some studies on BIV are focused on tat (Guo et al, 2013), vif (Zhang et al, 2014) rev (Gomez Corredor and Archambault, 2009;Gomez Corredor and Archambault, 2012) and others (Albernaz et al, 2015;Liu et al, 2015), very scarce attention has been paid to env. The Env of BIV is composed of two subunits: gp100, a surface subunit (SU) that binds host cell receptors, and gp45, a transmembrane subunit (TM) that ultimately inserts into the host cell membrane and promotes the fusion.…”
Section: Introductionmentioning
confidence: 99%